2016
DOI: 10.1021/acs.biochem.6b00539
|View full text |Cite
|
Sign up to set email alerts
|

Curvature Sensing by a Viral Scission Protein

Abstract: Membrane scission is the final step in all budding processes wherein a membrane neck is sufficiently constricted so as to allow for fission and the release of the budded particle. For influenza viruses, membrane scission is mediated by an amphipathic helix (AH) domain in the viral M2 protein. While it is known that the M2AH alters membrane curvature, it is not known how the protein is localized to the center neck of budding virions where it would be able to cause membrane scission. Here, we use molecular dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…However, the new virion also remains attached to the membrane as well as the previous virion by a small membranous neck. The continuation of this cycle and repeated initiation of budding results in the formation of consecutive scission-defective virions that resemble beads on a string [180,181]. The same morphology has been reported for the Moloney murine leukaemia virus upon deletion and mutation of p12 protein that functions in its assembly and release [182].…”
Section: Assembly and Budding: Scissionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, the new virion also remains attached to the membrane as well as the previous virion by a small membranous neck. The continuation of this cycle and repeated initiation of budding results in the formation of consecutive scission-defective virions that resemble beads on a string [180,181]. The same morphology has been reported for the Moloney murine leukaemia virus upon deletion and mutation of p12 protein that functions in its assembly and release [182].…”
Section: Assembly and Budding: Scissionsupporting
confidence: 58%
“…In the absence of scission machinery, the budding process begins but ultimately stops, and render budding virions attached to the membrane by a small membranous neck. This causes virions to have an uncharacteristically elongated morphology sometimes referred to as "beads-on-a-string" and is seen in viruses that lack the necessary machinery to release the budded virion [179][180][181][182][183]. This is clearly and elegantly demonstrated in the mutation of the matrix-2 (M2) protein, a viral protein responsible for the budding and scission of the influenza virus.…”
Section: Assembly and Budding: Scissionmentioning
confidence: 99%
“…We note that while equation (5) describes a mean-field treatment, figure 4 does not invoke the mean-field approximation and in that sense is an exact (albeit numerically evaluated) result for μ ex ( n P ). Still, the mean-field picture of the membrane protein interactions described above is a good description of the curvature sensing behavior of the CRP, which is demonstrated experimentally by measuring protein localization to predeformed regions on the cell membrane [69, 102, 140144]. …”
Section: Membrane Remodeling At the Mesoscalementioning
confidence: 99%
“…Several CRPs including BAR and ENTH domains are sensitive to the curvature of membranes adhered to wavy substrates [100]. The large-scale ENTH domain simulations show that they adjust their local order to match the anisotropy of their substrates [97] while simulations performed on buckled bilayers demonstrate that amphipathic helices can sense curvature and lipid packing defects [101, 102]. …”
Section: Introductionmentioning
confidence: 99%
“…At the C-terminus of each there is an amphipathic helix (35), and recent work has shown that both M2 and the M2 AH amphipathic peptide can serve to facilitate budding and scission of filamentous virions (36,37). Moreover, the M2 AH peptide construct retains significant function in membrane remodeling (38) and curvature sensing (39). A correspondence between models of the full-length M2 protein, the M2 construct lacking the extended C-terminal cytoplasmic tail (but including the AHs), and the M2 AH peptide is therefore reasonable in the study of M2's role in budding and scission.…”
Section: Cg Model and Correspondence With In Vivo And In Vitro Systemsmentioning
confidence: 99%